Monitorización del pastoreo de bovinos del CIDBA – Acraquia a través de redes de sensores inalámbricos - Paucar Chanca, Rufino (2024)
The objective of this work was to understand the grazing behavior of cattle at the Acraquia Cattle Research and Development Center (CIDBA) of the National University of Huancavelica, through wireless sensor networks. To do this, a wireless sensor network device connected to a web application (in charge of managing the information captured by the device) was designed, built and implemented. This system (device and web application) included sensor nodes in each cattle (collar with its respective power sources) and a monitoring station, which allowed collecting real-time data on the location, movements and behavior of the cattle. The information obtained was processed and analyzed to know the movement, grazing time, drinking times and sleeping time of the CIDBA cattle. The following values were found as the general average for the variables under study: displacement = 276 meters, grazing time = 8.26 hours, sleeping time = 11.35 hours and the cows' drinking time ranged between 08:55 hours and 10:05 hours in the morning and from 12:59 hours to 14:15 hours in the afternoon. On the other hand, the results show the effectiveness of the system in generating accurate and useful data for decision making in grazing management. Likewise, challenges associated with geographic and climatic conditions, as well as maintenance of equipment in the field, were identified. In conclusion, the use of wireless sensor networks represents an innovative and efficient tool to improve grazing management in livestock systems, contributing to sustainable development and the conservation of natural resources. It is recommended to strengthen the technological infrastructure, train users and promote integration with sustainable management programs.